P.085 Perioperative endovascular procedure utilization in transsphenoidal surgery patients at two tertiary-care academic centres. (5th June 2019) - Huynh, TJ; Cusimano, M; Clarke, DB; Weeks, A; Marotta, TR; Maloney, WJ; Aldakkan, A; Bharatha, A
Abstract : Background: Utilization of endovascular procedures in the perioperative management of patients undergoing transsphenoidal surgery is uncommon but plays a critical role in preventing and treating potentially life-threatening vascular complications.Methods: We performed a retrospective review of all patients over a 10-year period who underwent transsphenoidal surgery at two tertiary-care institutions and identified all pre-operative and post-operative endovascular procedures performed.Results: 18 perioperative endovascular procedures were performed including 9 pre- and 9 post-operative. Pre-operative procedures included balloon-test occlusion (n=4), aneurysm coiling (n=4), and parent artery occlusion (n=1). One aneurysm coiling was complicated by coil migration requiring coil retrieval with a snare device and one balloon-test occlusion was complicated by pituitary apoplexy. Pituitary apoplexy following balloon-test occlusion has not been reported and the potential pathophysiology is reviewed. Post-operative procedures included embolization for epistaxis (n=2) and embolization with or without parent artery sacrifice for carotid and anterior cerebral artery vascular injury (n=7). Arterial vascular injury was managed with coil embolization and/or with detachable balloons. Review of anatomical features predisposing to vascular injury are discussed.Conclusions: Patients undergoing transsphenoidal surgery should be managed with a multidisciplinary team ensuring that endovascular treatment options are made available during the perioperative period.